2022
DOI: 10.14814/phy2.15227
|View full text |Cite
|
Sign up to set email alerts
|

Daily injection of melatonin inhibits insulin resistance induced by chronic mealtime shift

Abstract: Shift work disorders have become an emerging concern worldwide. Shift disorders encompass a wide range of illnesses that have yet to be identified. The study focused on the relationship between shift work disorders and insulin resistance. Previously, it was reported that advancing the usual mealtime of mice triggered insulin resistance. Here, the hypothesis that chronic mealtime shifts induce oxidative damage leading to chronic diseases such as type 2 diabetes was tested. It was found that mealtime shift cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Oxidative stress is defined as the imbalance in the production/generation of free radicals or ROS/RNI at a rate that exceeds the scavenging or protective activity of the body’s endogenous antioxidant mechanisms e.g., superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and blockers of lipid peroxidation [18] , [26] , [111] , [112] . To exert its anti-oxidative effects and confer protection against oxidative stress, PCA up-regulates the activities of endogenous antioxidant systems and attenuates pro-oxidant systems [19] .…”
Section: Antioxidant Property Of Pca and Dox Treatmentmentioning
confidence: 99%
“…Oxidative stress is defined as the imbalance in the production/generation of free radicals or ROS/RNI at a rate that exceeds the scavenging or protective activity of the body’s endogenous antioxidant mechanisms e.g., superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and blockers of lipid peroxidation [18] , [26] , [111] , [112] . To exert its anti-oxidative effects and confer protection against oxidative stress, PCA up-regulates the activities of endogenous antioxidant systems and attenuates pro-oxidant systems [19] .…”
Section: Antioxidant Property Of Pca and Dox Treatmentmentioning
confidence: 99%
“…Throughout the experiment, food was made available during the light hours, a time when mice would normally be resting, thus impeding their ability to achieve complete rest. The design of this experiment was based on a model that our group described previously in published work [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that advancing mealtimes by 6 hours for a 4-week period in mice significantly improves antioxidant capacity during the early night, concomitant with increased levels of reactive oxygen species [ 14 ]. These changes lead to an imbalance between oxidative stress and antioxidant activity, indicating a potential increase in oxidative damage during the light phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations